IDENTIFIKASI JAMUR Aspergillus Sp. PADA DEBU AC (AIR CONDITIONER) DI JURUSAN ANALIS KESEHATAN POLTEKKES KEMENKES BENGKULU TAHUN 2025 - Melita Agustina; Laksono, Heru; Putra Adi Irawan (Poltekkes Kemenkes Bengkulu, 2025)
AC (Air Conditioner) is an electronic air conditioner that uses water and condensate to provide coolness for those in the room, and protects humans from exposure to outdoor air pollution. The use of Air Conditioner can increase comfort and work productivity, but Air Conditioner that is rarely cleaned will be a comfortable place for microorganisms to attach and breed. Microorganisms can be mold, fungi, protozoa, viruses and bacteria. Aspergillus fungus is in the Ascomycetes classification which can be found anywhere. Grows as a saprophyte in various rotten plants and in organic dust. The presence of Aspergillus Sp fungus, especially in the Ac unit, is important because Aspergillus Sp can infect the respiratory tract. Aspergillus Sp fungus can be found in environments with high humidity, such as dirty AC filters. The spores spread in the air openly through Ac circulation and inhalation cannot be prevented and can enter from the respiratory tract to the lungs. This study aims to identify Aspergillus Sp fungi in Ac (Air Conditioners) at the Health Analyst Department of the Ministry of Health Polytechnic of Bengkulu in 2025.